Peran Kader Dalam Memotivasi Ibu Balita Yang Berkunjung Ke Posyandu - Widyaningsih, Tri Sakti; Windyastuti, Windyastuti; Tamrin, Tamrin (Jurnal Keperawatan, 2020)
Integrated service post as one of the health services that serves to facilitate public especially for pregnant women and toddlers to implement happy little family. This study aims to determine the relationship between the role of cadres and the motivation of mothers who visit Posyandu, Tambakharjo Village, West Semarang District. This research used Cross Sectional. The sample was 39 people. The sampling technique used purposive sampling. Statistical test using Rank Spearman correlation. The results show that a relationship between the role of cadres and maternal motivation = 0.565 and p-value = 0,000 (<Î± = 0.5). The meaning is that, the stronger the role of the posyandu cadre under five, the higher the motivation of mothers under five to visit the posyandu. Recommendation: providing information about the role of cadres and the Posyandu program for under-fives, it is expected that mothers will have the motivation to visit the Posyandu RW VII, Tambakharjo Sub-District, West Semarang District.